Chemotherapy for trypanosomiasis. Proceedings of a workshop - Peregrine, A.S. (International Livestock Research Institute, 1990)
In light of the current problems and limitations of chemotherapy for trypanosomiasis in domestic livestock and human beings, this workshop was conducted to discuss research aimed at developing new trypanocides. Because of the scarcity of information on the phenotypic and genetic basis of drug resistance in trypanosomes, work on other protozoan parasites was also reviewed for its potential relevance to the development of new therapeutic agents and diagnostics for typanocide resistance. The meeting highlights areas of trypanosomal chemotherapy research in which developments are being made as well as areas where more research is required. Topics of discussion include trypanosomal metabolic pathways - targets for trypanocides; drug resistance, and new drug delivery systems. The last chapter presents country reports country reports on Tanzania, Scotland, Canada, Nigeria, Ethiopia, Kenya, and Indonesia.